30 years after the fall of Communism: Lessons learned for inward FDI - Zbigniew Zimny (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2023)
Accomplishing a goal widely shared by emerging economies but achieved by few, East European countries attracted large amounts of FDI, especially export-oriented FDI, easing their transition from communist into market economies. This Perspective highlights key factors behind the EU11's success and draws potential lessons for other countries.
Keywords: 330